2022
DOI: 10.3390/agronomy12010206
|View full text |Cite
|
Sign up to set email alerts
|

Control of Substrate Water Availability Using Soil Sensors and Effects of Water Deficit on the Morphology and Physiology of Potted Hebe andersonii

Abstract: Many plant producers tend to overwater crops to prevent water stress and salt-induced damage. These practices waste irrigation water and cause leaching that harms the environment and increases production costs. In order to optimize water consumption and minimize the environmental impact of plant production, this study aimed to determine the physiological and morphological responses of Hebe andersonii to three substrate volumetric water contents (49%, 39%, and 32%). The experiment was conducted in a greenhouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 88 publications
(110 reference statements)
0
2
0
Order By: Relevance
“…Zhang et al [21] found that q p decreased markedly in response to drought and waterlogging stress, accompanied by reductions in ETR and Y (II) . Bañón et al [22] also reported that ETR of Hebe andersonii decreased with the decrease in substrate volumetric water content, while NPQ was the highest under more severe water-deficit conditions. Higher values of NQP were observed under water stress as a result of energy dissipation [26,67].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Zhang et al [21] found that q p decreased markedly in response to drought and waterlogging stress, accompanied by reductions in ETR and Y (II) . Bañón et al [22] also reported that ETR of Hebe andersonii decreased with the decrease in substrate volumetric water content, while NPQ was the highest under more severe water-deficit conditions. Higher values of NQP were observed under water stress as a result of energy dissipation [26,67].…”
Section: Discussionmentioning
confidence: 91%
“…Photosynthesis is closely related to stomatal conductance, and both are extremely sensitive to water restriction [14,[17][18][19]. Irrigation schedules based on the relationship between photosynthesis and SMC in container nurseries have received considerable attention [12,15,[20][21][22][23]. For example, when the irrigation requirements of landscape roses were determined according to growth and photosynthetic responses to SMC, the shoot and root dry matter, net photosynthetic rate (P n ), stomatal conductance (g s ), and transpiration rate (T r ) were highest at 30% to 40% SMC [12].…”
Section: Introductionmentioning
confidence: 99%
“…When density or thickness increases, leaves have higher photosynthetic activity per unit weight due to a higher density of pigments, proteins, and other metabolites [41], and lower water loss due to less surface available for transpiration [42]. Previous studies indicated that potted Hebe plants exposed to severe water stress increased their leaf thickness [15]. It has been suggested that reduced stomatal density and pore size may be a mechanism to reduce plant transpiration under saline conditions [43,44].…”
Section: Plant Growth and Visual Qualitymentioning
confidence: 99%
“…A recent study has indicated that H. andersonii cv. Variegata can successfully grow under low substrate moisture and non-leaching conditions [15].…”
Section: Introductionmentioning
confidence: 99%
“…Throughout this Special Issue, some of the stresses mentioned above, as well as the resistance mechanisms implemented at different stages of the vegetative and reproductive cycles of plants (seed, seedling, adult plant or fruit), will be discussed, including: a review regarding oxidative stress, ageing and methods of seed invigoration; a study on how to control the availability of water in substrate and water deficit responses in variegata, a type of ornamental plant; an analysis of the postharvest quality of peach fruit under optimal and stressful temperatures; a review concerning nutritional disorders related to the macronutrient calcium and strategies to avoid them, such as soilless production systems; the salt stress resistance of soapwort, a native Chinese plant; responses to heat stress in basil plants; drought stress responses of Chinese Melia azedarach of different origins; responses to UV and cold stress in rice plants associated with the expression of genes associated with the production of phytoalexins; an electron microscopy analysis of histological changes in wheat plants due to salinity; an analysis of the resilience of oilseed grown in greenhouses under stress conditions which simulate the future climate change scenario, using a variety of techniques; and a study of the different responses of field bean to the application of electromagnetic fields [1][2][3][4][5][6][7][8][9][10][11][12].…”
mentioning
confidence: 99%